Coding of PPM based modulation techniques to improve the performance of infrared WLAN's - Alves, Rui
In this communication we consider the use of PPM based modulation methods, such as the hybrid modulation method called Amplitude and Pulse-Position Modulation (APPM) and Overlapping Pulse-Position Modulation (OPPM), to improve the performance of Infrared WLAN’s. The bandwidth eficiency expressions of these modulation schemes are presented and compared against the one of Pulse-Position Modulation (PPM), which allows to conclude that both APPM and OPPM can be used to improve the performance of PPM without significant bandwidth expansion, using Trellis-Coded Modulation (TCM) codes. We also derive the best codes for some APPM and OPPM schemes, and the results show that non-negligible coding gains without bandwidth expansion can be obtained with trellis codes of moderate complexity.